2017
DOI: 10.1136/jech-2016-208105
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses of sexual abuse and their common registered comorbidities in the total population of Stockholm

Abstract: Diagnoses of drug and alcohol abuse, psychotic, bipolar, stress anxiety disorders, depression and somatic pain are more common among individuals with a diagnosis of sexual abuse than among individuals without a diagnosis of sexual abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
(24 reference statements)
4
13
0
Order By: Relevance
“…New technique and electronic journal records have opened up new possibilities for analyzing healthcare data. In 2017, we replicated prior results, and quantified with real numbers by a register-based study including over 2 million persons in Stockholm Region, Sweden [17]. The odds for stress-related diagnoses and depression were tenfold higher among those with a sexual abuse (SA) experience registration, compared to those without SA experience registration [17].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…New technique and electronic journal records have opened up new possibilities for analyzing healthcare data. In 2017, we replicated prior results, and quantified with real numbers by a register-based study including over 2 million persons in Stockholm Region, Sweden [17]. The odds for stress-related diagnoses and depression were tenfold higher among those with a sexual abuse (SA) experience registration, compared to those without SA experience registration [17].…”
Section: Introductionsupporting
confidence: 57%
“…In 2017, we replicated prior results, and quantified with real numbers by a register-based study including over 2 million persons in Stockholm Region, Sweden [ 17 ]. The odds for stress-related diagnoses and depression were tenfold higher among those with a sexual abuse (SA) experience registration, compared to those without SA experience registration [ 17 ]. However, in that study, the comorbidities and the registered SA experience were collected in the same time frame.…”
Section: Introductionmentioning
confidence: 54%
“…The high risk of re-victimization after CSA in combination with delayed disclosure, also makes it plausible that some of the cases with their first diagnosis of sexual abuse registered at Södersjukhuset in Stockholm had experiences of CSA prior to the sexual abuse that resulted in the visit to the clinic. This assumption is also supported by research that has shown a 25% higher amount of reports on sexual assaults to the police, than diagnoses of sexual abuse recorded within the health care system, for the same population during the same period of time [ 28 ].…”
Section: Discussionmentioning
confidence: 77%
“…However, in 2017 we presented a register-based study including over two million persons in Stockholm replicating prior results, and also quantifying the results with real numbers and their relative magnitude in comparison with the general population in the Stockholm Region, Sweden. In this study, adolescent girls represented more than half of all cases, and the odds for stress-related diagnoses and depression were tenfolds higher among these girls than in those without a diagnosis of sexual abuse [28]. A limitation to this study was that the co-morbidities and the registered diagnoses of sexual abuse were collected in the same time frame.…”
Section: Introductionmentioning
confidence: 89%
“…Implicit in this language is the assumption that survivors of sexual violence are always female. Although statistics show that females are more likely to be victimised (Asgeirsdottir et al, 2011;Rajan et al, 2017), male survivors do exist, and they are somewhat excluded from this community of survivors. The digital aspect may also exclude older adults.…”
Section: Discussionmentioning
confidence: 99%